Research and Analysis of Explosion-Proof Diesel Engine Performance Based on Different Exhaust Gas Cooling Systems - Zhiyuan Shi; Hongxin Wei; Guanghui Li; Yuan Wang; Quanming Li; Xin Zheng; Kunhao Song; Chong Chen; Chi Ma; Samsil Arefin Mozumder; Md Khairul Basher (Energies, 2025)
As stringent emission regulations and safety standards for explosion-proof diesel engines become more critical, the demand for efficient exhaust cooling systems has increased. Traditional cooling systems, typically relying on cooling and purification water tanks, have limitations in terms of safety, performance, and emissions control. To address these challenges, a novel dry exhaust gas cooling system was developed, incorporating a heat exchanger and exhaust dilution cooling device, replacing the conventional water-based cooling systems. This study explores the performance of the dry exhaust gas cooling system through a series of experiments including explosion-proof testing of the exhaust system, whole machine explosion-proof testing, exhaust temperature measurements, surface temperature evaluations, and exhaust gas composition analysis. The system’s performance was compared to both wet and combined dry + wet exhaust gas cooling systems. Results showed that the dry exhaust cooling system maintained its explosion-proof integrity during all tests, with the highest exhaust temperature at 68.5 °C and a surface temperature of 130.8 °C—both of which comply with safety standards. Notably, the dry exhaust system also demonstrated improved power output and reduced fuel consumption by over 4% compared to the other systems. Furthermore, it significantly lowered harmful exhaust emissions, reducing CO, HC, NOX, and CO2 levels by 55%, 71%, 68%, and 82%, respectively, when compared to the wet exhaust cooling system. In comparison to the dry + wet system, these reductions were even more pronounced—63%, 75%, 66%, and 94%, respectively. The findings suggest that the dry exhaust gas cooling system offers a safer, more efficient, and environmentally friendly alternative to conventional exhaust cooling systems in explosion-proof diesel engines.